Phylogeny of Urostylididae (Heteroptera: Pentatomoidea) reveals rapid radiation and challenges traditional classification - Duan, Yujie; Fu, Siying; Ye, Zhen; Bu, Wenjun (Zoologica scripta, 2023)
Urostylididae, a phytophagous heteropteran family that feeds on the sap of various trees and shrubs, comprises 8 genera and 173 species. Its phylogeny has received little attention, and no studies have revealed its generic monophyly or relationships. We present the first molecular phylogeny of Urostylididae based on complete mitogenomes and nuclear ribosomal genes from almost all genera and representative species, using maximum likelihood analysis and Bayesian inference. All phylogenetic results showed overall consistent topological relationships, indicating polyphyly of the three most speciose genera, Urolabida, Urochela, and Urostylis. Among the three monotypic genera, Chelurotropella formed a stable relationship with Urochela wui in all trees, Cobbenicoris was a stable sister group of Urostylis fici but with position variation among trees, and Urochellus formed a sister group with Urostylis cuneata or species of two or more genera in different trees. The smaller genus Tessaromerus was always sister to Urostylis tricarinata, but their positions varied among trees. Thus, the currently recognized genera of Urostylididae are unreliable. Furthermore, our phylogenetic results suggested some topological incongruence among the trees produced with different analytical methods and data sets, mainly among deep internal nodes, with short branches and low support values. Given the quartet‐based evaluation system and branch patterns, Urostylididae underwent rapid radiation resulting in incomplete lineage sorting and introgression in our data sets, making our phylogenetic analyses more sensitive to the data or method used. Moreover, the rapid radiation might have caused morphological homoplasy of diagnostic characters of genera, leading to taxonomic confusion for Urostylididae. Therefore, a thorough taxonomic revision of this family is needed.